The role of concha bullosa in chronic rhinosinusitis: our experience at a tertiary care hospital - Fathima, Afshan; Arabhanvi, Ramappa; Shamanna, Karthik; Joy, Lyra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic rhinosinusitis (CRS) is a common and persistent illness that otorhinolaryngologists encounter commonly. It is an important cause of morbidity and accounts for major loss of income. Anatomical variations of the lateral wall of the nose have been reported which can predispose to CRS. The aim of the present study was to determine the percentage of concha bullosa in patients with CRS and to ascertain its relationship with chronic rhinosinusitis. Methods: 100 patients attending the ENT outpatient department, Bangalore Medical College and Research Institute between December 2018 and 2019 were included in the study. Patients clinically diagnosed as CRS underwent diagnostic nasal endoscopy (DNE) and computed tomography (CT) scan of nose and paranasal sinuses, following which the relationship between concha bullosa and CRS was determined. The results were tabulated in excel sheet. Chi square test was applied for qualitative data. Results: Of the 100 patients of CRS, 40 were males and 60 females. Of the 40 male patients, 16 showed presence of concha bullosa and of the 60 female patients, 28 showed concha bullosa. Headache (92%) was the most common presenting symptom in our study. A statistically significant correlation was noted between the presence of concha bullosa and chronic maxillary sinusitis (p value <0.05). Conclusions: Concha bullosa is one of the most common anatomical variations of the lateral wall of the nose. The presence of concha bullosa plays a significant role in the development of chronic rhinosinusitis particularly in chronic maxillary sinusitis.